Pan Soplica jako maska pseudonimu Henryka Rzewuskiego - Paweł Dudziak (Przestrzenie Teorii)
Traditionally spoken genre, which in the 17th and 18th centuries was the noblemen's tale, became in the 19th century a written form of tale, i.e. Pamiątki Soplicy [The memoirs of Soplica] of Henryk Rzewuski. The genre description of tale has always presented troubles to literary scholars - an attempt at capturing its distinctive features are usually not very precise or discussed from too many aspects. Studies on the tale should be started from the new recognition of the status of the tale „narrator" in the model realisation of the genre, i.e. Pamiątki Soplicy [The memoirs of Soplica]. The thesis of this article is: narrator - Seweryn Soplica - is Henryk Rzewuski's pseudonym; a pseudonym which allows him to better and more effectively describe the presented, but the already non-existent Sarmatian world of the 18th century.